Legal Provisions for Wife's Right to Live After Divorce in the Pasuruan Religious Court - Supaat, Joko; Muhibbin, Moh; Suratman, Suratman (Jurnal Ilmiah Penegakan Hukum, 2024)
This research goes in-depth into aspects of determining the amount of maintenance, factors that influence court decisions, and legal considerations that are the basis for determining maintenance rights. In the context of the Pasuruan Religious Court, this research also explores legal practices and the court's views on cases of wives' maintenance rights after divorce. Religious Courts are a form of application of Islamic law in the law enforcement system in Indonesia, as intended by Law No. 7 of 1989 concerning Religious Courts, which was later amended by Law No. 3 of 2006 and last amended by Law No. 50 of 2009. This research is a type of empirical juridical research. The approach used in this research is a sociological-legal approach, with the data in the form of primary and secondary data. The writing technique is carried out using interviews and document studies, while the data analysis is qualitative and descriptive. From the results of the research, it was found that enforcement of the wife support law at the Pasuruan Religious Court has been made as much as possible by implementing the orders of the Law and Regulations of the Supreme Court of the Republic of Indonesia. This is for the sake of upholding justice for wives whose husbands divorced. However, there is still a legal loophole that can be used by the husband to avoid paying his wife's maintenance, which has been imposed in the court decision. Even though many legal instruments have been created to protect and ensure women's rights are fulfilled, in practice, there is still a lot of neglect of women's rights.